Stenosed carotid bifurcation: hemodynamics and wall shear stress - Luísa C. Sousa (2013)
The goal of this work is to present a semi-automatic methodology for patient-specific study of carotid bifurcation hemodynamics using Doppler ultrasound images. A good agreement between ultrasound imaging data and computational simulated results was obtained.